PENGKLASIFIKASIAN HAK ATAS MEREK SEBAGAI BENDA PADA OBJEK JAMINAN DALAM PERBANKAN - Muhammad Hadi Alhadar (Fakultas Hukum Universitas MyhammadiyahTapanuli Selatan, 2021)
Trademarks are used in determining or distinguishing a mark where the brand gives the right to the owner of the mark, to be used in trading activities and services within the scope of business. Article 1131 of the Civil Code explains that all objects can be used as collateral, but the absence of authorization regarding a mark is a mark and can be used as a guarantee. So in this study is based on the problem of whether a brand can be classified as an object and then used as an object of guarantee by looking at the economic value contained in the brand and the characteristics of the brand. This research was conducted to explain how the brand qualifier as an object can be used as an object of guarantee. Furthermore, this research also intends to explain what form of assurance is appropriate to apply to the rights to a brand. The final results of this study explain that a brand can be said to be an object because it has material characteristics in its characteristics, therefore a brand can be used as an object of collateral at a bank, however, in practice some banking institutions apply a brand. as a guarantee just make a guarantee of a brand additional guarantee and yet. used as the main guarantee because there is no reference to standardize the exact value of the brand.